1994
DOI: 10.1002/bjs.1800811218
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with epirubicin, cisplatin and 5-fluorouracil for the palliation of advanced gastric and oesophageal adenocarcinoma

Abstract: The palliative efficacy of laser therapy with combination chemotherapy (cisplatin, epirubicin and continuous infusion of 5-fluorouracil) was assessed in 34 patients with inoperable gastro-oesophageal cancer. Comparison was made with a group of 30 patients treated previously by laser alone. Twenty patients responded to chemotherapy. There was a significant improvement in dysphagia, as measured by a decreased laser requirement to maintain satisfactory swallowing. In this non-randomized prospective phase II trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…245 Addition of epirubicin may improve the palliative benefit 246 with a reduction in repeat laser requirements. 247 A similar benefit is achievable in squamous carcinoma. 246 Early results with paclitaxel, which is also a radiosensitiser, show response rates of 48-70% in combination with cisplatin, with or without 5-FU, including 12-23% complete response.…”
Section: Palliative Chemotherapymentioning
confidence: 88%
“…245 Addition of epirubicin may improve the palliative benefit 246 with a reduction in repeat laser requirements. 247 A similar benefit is achievable in squamous carcinoma. 246 Early results with paclitaxel, which is also a radiosensitiser, show response rates of 48-70% in combination with cisplatin, with or without 5-FU, including 12-23% complete response.…”
Section: Palliative Chemotherapymentioning
confidence: 88%
“…Several studies looking at neoadjuvant and palliative chemotherapy reported that those patients who responded to treatment had an improved survival outcome [4][5][6][7][8][9] with neo-adjuvant regimens having a response rate, at best, of 50-60% [1]. Studies clearly demonstrate that those who do not respond to neoadjuvant chemotherapy have a significantly worse prognosis than those who have surgery alone [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical and radiation therapy are not used frequently in the palliative treatment of malignant dysphagia due to their high morbidity and mortality as well as prolonged hospitalization (3, 6, 15). Chemotherapy, although useless when used alone, has been reported to reduce the number of laser therapy sessions when performed in conjunction with laser therapy (8). Endoscopic laser therapy, based on the principle of tumor destruction with thermal energy, may restore almost normal swallowing function with a low complication risk (9).…”
mentioning
confidence: 99%